In vitro biocompatibility assessment of sulfonated polyrotaxane-immobilized polyurethane surfaces - Parl, HD; Lee, WK; Ooya, T; Park, KD; Kim, YH; Yui, N (WILEY-LISS, 2003)
Sulfonated polyrotaxanes (PRx-SO3's), in which sulfonated alpha-cyclodextrins (alpha-CDs) were threaded onto the poly(ethylene glycol) (PEG) segments in a PEG-b-poly(propyleneglycol) (PPG)-b-PEG triblock copolymer (Pluronic) capped with benzyloxycarbonyl (Z)-L-phenylalanine (Z-L-Phe), were prepared as a novel surface-modifying biomaterial. Surface modification of the polyurethane (PU) was carried out by blending the PRx-SO3's with a PU solution, followed by solution casting. The incorporated PRx-SO3's led to the enhanced hydrophilicity by changing the surface properties of the PU matrix. Modified PUs showed the stable entrapment of the PRx-SO3's with little extraction into water and enhanced mechanical properties after exposure to water compared to the PU control. The incorporated PRx-SO3's repelled the proteins and kept them from closely approaching the surface areas, prevented platelet activation by thrombin, and effectively repelled bacteria. These results suggest that both the supramolecular structure of the polyrotaxanes and exposure of the sulfonated groups onto the surfaces contribute to these phenomena. Thus, surface modification with PRx-SO3's is suggested to be useful for the fabrication of biocompatible medical devices.
Keywords: PROTEIN ADSORPTION; BIODEGRADABLE POLYROTAXANES; POLY(ETHYLENE OXIDE); BACTERIAL ADHESION; DRUG-DELIVERY; POLYMERS; CYCLODEXTRINS; TISSUES